Possible role of mitochondrial K-ATP channel and nitric oxide in protection of the neonatal rat heart - Doul, Jan; Miková, Dana; Rašková, Marcela; Ošťádalová, Ivana; Maxová, Hana; Ošťádal, Bohuslav; Charvátová, Zuzana (Molecular and cellular biochemistry, 2019)
Cardioprotective effect of ischemic preconditioning (IPC) and ischemic postconditioning (IPoC) in adult hearts is mediated by mitochondrial-K-ATP channels and nitric oxide (NO). During early developmental period, rat hearts exhibit higher resistance to ischemia-reperfusion (I/R) injury and their resistance cannot be further increased by IPC or IPoC. Therefore, we have speculated, whether mechanisms responsible for high resistance of neonatal heart may be similar to those of IPC and IPoC. To test this hypothesis, rat hearts isolated on days 1, 4, 7, and 10 of postnatal life were perfused according to Langendorff. Developed force (DF) of contraction was measured. Hearts were exposed to 40 min of global ischemia followed by reperfusion up to the maximum recovery of DF. IPoC was induced by 5 cycles of 10-s ischemia. Mito-K-ATP blocker (5-HD) was administered 5 min before ischemia and during first 20 min of reperfusion. Another group of hearts was isolated for biochemical analysis of 3-nitrotyrosine, and serum samples were taken to measure nitrate levels. Tolerance to ischemia did not change from day 1 to day 4 but decreased on days 7 and 10. 5-HD had no effect either on neonatal resistance to I/R injury or on cardioprotective effect of IPoC on day 10. Significant difference was found in serum nitrate levels between days 1 and 10 but not in tissue 3-nitrotyrosine content. It can be concluded that while there appears to be significant difference of NO production, mito-K-ATP and ROS probably do not play role in the high neonatal resistance to I/R injury.
Keywords: Tolerance to ischemia; 3-Nitrotyrosine; Ischemic Postconditioning; Potassium Channels; novorozená zvířata; reperfuzní poškození myokardu; oxid dusnatý; krysa rodu Rattus; ischemický postconditioning; Myocardial Reperfusion Injury; zvířata; Nitric Oxide; draslíkové kanály; potkani Wistar; Animals, Newborn; Neonatal rats; Mito-K-ATP channel; Rats, Wistar; Male; Nitrates; Ischemic postconditioning; Rats; Animals; mužské pohlaví